The red-cell 'X'-protein system in goats - evidence for a 3rd allele in a Malaysian breed - Hasima, N.; Dhaliwal, S.S.; Mukherjee, T.K. (1988)
Genetic polymorphism of the 'X'-protein in red cells from Malaysian Katjang goats was demonstrated by starch gel electrophoresis at pH 7.3. Two new phenotypes were observed, suggesting that one new allele is involved. A new nomenclature for the 'X'-protein system in goats is proposed.